Trabalhadores migrantes: no eito da cana à escravidão contemporânea em Goiás - Silva, Cristiane Passos Melo e (2014)
The proposal of this dissertation is to analyze the point of view of rural workers enslaved in contemporary times, the social relations established in these spaces of usurpation of freedoms and rights, as well as in other occupied workspaces, such as the Brazilian sugarcane fields. Hence the necessity of analyzing concepts pertinent to the development of the study, such as: peasants, identitary elements of peasantry, and contemporary slavery, among others. Within this context, I seek to analyze the history of domination undertaken in rural areas through the years, and the peasant moral code that persisted through time in the collective imaginary of rural populations, sustaining their process of resistance, in order to maintain a traditionally established and productive social practice. Categories such as race and gender will also be addressed in the course of this study, as well as others that proved relevant to the analyses presented here. Labor relations and the rights of these workers, likewise, were analyzed in the text, and the presence of rural labor unions and other representative organizations, in the daily work of these categories. The study will also include analyses which refer to the maintenance of the hierarchical segmentation in the workspace, the elements that motivate it, as well as the acts of violence practiced on workers over the years.